Examining the mining sector's contributions to gross domestic product and employment creation in the South African economy - Benard, Ndansi (My University, 2018)
South Africa holds an estimated value of US$2.5 trillion of non-energy, in-situ mineral wealth, making it the world’s wealthiest mineral resource-rich nation. The presence of these abundant mineral resources creates potential for sustained growth and development, such as in revenue generation, gross domestic product (GDP), employment creation, and foreign direct investment (FDI). However, the mining sector continues to face major challenges, including commodity price volatility, labour unrest, weak institutional framework, shortage of skilled labour, and other structural challenges. As a result, mining’s contributions to GDP and employment creation has witnessed significant downturn over the years. For instance, its contribution to GDP dropped from 21% in 1970 to 7.3% in 2016, while employment numbers in the sector declined by 17% between 1997 and 2009. It has equally failed to benefit many South Africans, and the country continues to suffer from socio-economic challenges such as high unemployment rates, income inequalities, high levels of poverty, and slow economic growth rates. It is in line with the above views that this study was centred on examining mining’s contributions to GDP and employment creation in South Africa over the period 1993 to 2015. Data was sourced from credible sources such as the Chamber of Mines of South Africa, the World Bank, and Quantec. Findings revealed that mining’s contributions to the overall GDP and employment creation in the South African economy witnessed significant decline over the period under review. This can be attributed to a decline in gold sector’s contribution to GDP and employment creation. Yet whilst gold mining showed a sharp decline, the study also found that the contributions of platinum group metals (PGMs), coal, and iron ore to the share of mining GDP and employment numbers increased steadily during the period under review. Efforts to improve mining’s contribution to long-term growth and addressing the developmental needs of the South African economy have seen the creation of measures such as the Mining Phakisa initiative, Africa Mining Vision (AMV), National Development Plan (NDP), Mining Vision 2030 goals, robust mineral policy, and the Mining Charter.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Engineering Johannesburg, 2018
Keywords: Gross domestic product; Economic history